Effective Communication in Deradicalization of Ex-Terrorism Convict - Mukorobin, Ustad; Sulaiman, Adhi Iman; Sutikna, Nana (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Terrorism always creates social, economic, and political chaos. Acts of terrorism in Indonesia are generally caused by religious beliefs and radical understandings held by the perpetrators. Terrorist convicts still maintain this belief, so a special approach is needed to run the deradicalization process effectively. Therefore, this research discusses issues regarding applying effective communication in the deradicalization process for terrorism convicts. An effective communication approach is positioned to support apparatus programs in the deradicalization process. This study uses a phenomenological approach to understand better the views and experiences of terrorism convicts undergoing the deradicalization process. The aim is to find and analyze effective forms of communication in the deradicalization process for terrorism convicts. The results of this study indicate that effective communication in the deradicalization process for terrorism convicts can be achieved through an approach that involves real and continuous attention, dialogue that is very careful about religious understanding, avoiding the act of extracting information about terrorist networks from the Police and BNPT; as well as people involved in handling terrorism; and applying an empathetic communication approach in embracing terrorism convicts, so that they do not return to the same environment and get a decent life. This approach also aims to ensure that former terrorism convicts feel cared for and valued by society.